Valorization of Human Urine with Mixed Microalgae Examined through Population Dynamics, Nutrient Removal, and Biogas Content - Ermis, Hande; Gulhan, Unzile Guven; Akca, Mehmet Sadik; Çakır, Tunahan; Altinbas, Mahmut (Mdpi, 2023)
The majority of nutrients in municipal wastewater originate from urine. However, when flush water is used, the urine is diluted and mixed with other organic household waste, losing its high-value stream content. This study investigated the effect of source-separated human urine on the population dynamics, nutrient removal, growth, and biogas content of mixed microalgae grown in 250 L raceway ponds. Overall, a maximum biomass concentration of 1847 mg/L was reached, with up to 90% nitrogen and 80% phosphorus removal efficiencies, along with 254.96 L/kg vs. biogas production. The microbial community analysis identified Chlorella sorokiniana (Chlorophyta, Trebouxiophyceae) as the species with the highest abundance, after confirmation with four different markers (16S rRNA, 18S rRNA, 23S rRNA, and tufA). Moreover, principal component analysis was applied to capture the effect of environmental factors on culture diversity. The abundance of Chlorella sorokiniana increased almost sevenfold when the culture was exposed to open systems compared to the small-scale study carried out in 1 L Erlenmeyer bottles in laboratory conditions, both grown in urine and synthetic media (BBM). In conclusion, the present study contributes to the potential to valorize urine with microalgae by showing its high biogas content, and reveals that microalgae can adapt to adverse environmental conditions by fostering their diversity.
Keywords: microalgae; biogas; raceway pond; human urine; valorization; wastewater treatment